Effects of hygiene guidance associated or not to provision of hygiene devices on habits of denture wearers (Acta Scientiarum. Health Sciences, 2015)
Appropriate hygiene of dentures contributes to the maintenance of oral and systemic health. However, most of denture wearers had never been instructed on how to perform daily oral/denture care. The purpose of this study is to investigate the influence of a guidance material associated or not to the provision of hygiene devices and its effect on the habits of denture wearers. Forty- eight complete denture wearers were randomly divided into three groups. Group N received no guidance on how to clean and wear their dentures, group G received an illustrated leaflet and verbal complementary instructions and group GK received the same guidance as group G and a hygiene kit for denture cleaning. After a six to ten week period they responded to a ‘hygiene and wearing habits’ questionnaire. Chi-square test was used for statistical analysis considering p < 0.05. Brushing was the most frequent cleaning method, the majority of groups N and G used toothpaste. Participants of group G and GK presented low percentages of individuals with hygiene and wearing routine considered improper. The differences between groups in hygiene and wearing routine were statistically significant (p < 0.001). The proposed guidance material yielded better results when associated to provision of hygiene devices for denture cleaning.